Drug discovery for polycystic kidney disease - Sun Ying; Zhou Hong; Yang Bao-xue (Acta Pharmacologica Sinica, 2016)
In polycystic kidney disease (PKD), a most common human genetic diseases, fluid-filled cysts displace normal renal tubules and cause end-stage renal failure. PKD is a serious and costly disorder. There is no available therapy that prevents or slows down the cystogenesis and cyst expansion in PKD. Numerous efforts have been made to find drug targets and the candidate drugs to treat PKD. Recent studies have defined the mechanisms underlying PKD and new therapies directed toward them. In this review article, we summarize the pathogenesis of PKD, possible drug targets, available PKD models for screening and evaluating new drugs as well as candidate drugs that are being developed.